Privacy enhancing technologies 11th international symposium, PETS 2011, Waterloo, ON, Canada, July 27-29, 2011 : proceedings - Fischer-Hübner, Simone; Hopper, Nicholas (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 10th International Symposium, PETS 2011, held in Waterloo, Canada, in July 2011. The 15 revised full papers were carefully reviewed and selected from 61 submissions. The papers address design and realization of privacy services for the Internet, other data systems and communication networks. Presenting novel research on all theoretical and practical aspects of privacy technologies, as well as experimental studies of fielded systems the volume also features novel technical contributions from other communities such as law, business, and data protection authorities, that present their perspectives on technological issues.